Optimization of cyclic multiplex immunohistochemistry staining for fresh frozen brain tumor samples - Savola, Noora (2024)
Mapping the tumor microenvironment provides essential information about cancer diagnosis, progression, and possible treatments. Glioblastoma is the most common primary malignant brain tumor where tumor heterogeneity together with the tumor microenvironment cause ineffectiveness of treatments and poor prognosis of the disease. For this reason, a comprehensive mapping of the glioblastoma microenvironment and better understanding of the role of immune cells are key to studying the biology of the disease and developing new treatments. The microenvironment of glioblastoma consists of different cancer cell subtypes, different types of neural cells, local and infiltrating immune cells, and vascular endothelial cells and pericytes. The aim of this thesis was to optimize multiplex fluorescent immunohistochemistry staining for fresh frozen brain tumor samples to map the tumor microenvironment. The goal was to create a staining protocol which covers markers to identify the main cell types: the marker CD45 used to quantify immune cell infiltration, the T-cell markers CD3, CD4 and CD8, the macrophage marker CD163, macrophage and dendritic cell marker CD11c, the TMEM119 marker for distinguishing microglia from the macrophages infiltrating the tumor area, the endothelial cell marker CD31 for identifying blood vessels, and the Ki67 marker for evaluating cell proliferation. The durability and behavior of fresh frozen tissue and of the tissue section was tested in different staining phases. After this fresh frozen human glioblastoma samples were used to optimize antibodies and staining order for the final protocol. An optimized staining protocol for fresh frozen samples enables characterization of the tumor microenvironment of brain tumors together with sequencing-based spatial tissue analysis.